STRATEGI USTADZ DALAM MENINGKATKAN PEMAHAMAN KITAB FIQIH (MABADI’UL FIQHIYAH) SANTRI PONDOK PESANTREN AL-ANWAR SENGON PRINGGODANI BANTUR - Faizatus Sholiha, Muhammad Arif Nasruddin (PRODI PAI FIK UNIRA MALANG, 2024)
In Islamic boarding schools, Ustadz is one of the components that is very crucial for the implementation of the educational process. Its existence is the main actor as a facilitator in organizing the student learning process. This research was motivated by the researcher's interest in the strategies applied by ustadz to the learning of the book mabadi'ul fiqhiyah at the Al-Anwar Islamic Boarding School. The accuracy of strategy selection greatly determines the final learning outcomes. This research aims to explore the strategies that ustadz apply in this class. The research used is qualitative research with the type of ethnographic research. Data was collected through interviews with ustadz, ustadzah and students of the Al-Anwar Sengon Pringgodani Islamic Boarding School. Data collected through interviews, observation and documentation methods are then analyzed and presented. The participants in this research were ustadz and students of the Al-Anwar Sengon Pringgodani Islamic Boarding School who were involved in studying the book Mabadi'ul Fiqihiyah. The research results showed that the strategy implemented by the ustadz was appropriate for the students in this class, because the strategy was prepared and determined by the ustadz before the lesson, not while the lesson was taking place. What supports students' understanding is not only the students' abilities but also the ustadz's strategies. On average, students of the Mabadi'ul Fiqhiyah book have a high and medium level of understanding. There are 2 types of strategies used by Ustadz, namely: direct strategy and cooperative strategy.